Linguistic Aesthetics in the Market: Evidence from Oral Business Nepali - Poudel, Kamal Kumar; Acharya, Kushmila; Sharma, Netra Prasad (Advances in Social Sciences Research Journal, 2021)
Communication in business is usually supposed to be precisely and directly targeted at the message. The present study was instigated to answer whether, as generally assumed, communication in business excludes the artistic or poetic use of language meant for entertainment. Using observation, recording and field notes as the study techniques, a corpus of 24000 words was collected in Nepali from the major open market sites and business hubs located within Nepal. The corpus was then translated into English. As a delimitation of the study, the aesthetic aspect of language use and usage was particularly focused and analyzed. The exploration suggests that the users of oral business Nepali (OBN) commonly entertain themselves and others side by side as they speak while conducting business transactions. They commonly achieve this end by creating art and imagination, expressing and creating humor, and making associations. A future direction would be to extend the study in terms of its scope and methodology.